#### Answer

The Derivative is:
$\frac{ds}{dt}=\sec^2 t-1$

#### Work Step by Step

$s=\tan t - t$
Applying derivative rules:
$\frac{ds}{dt}=\frac{d}{dt}(\tan t)-\frac{d}{dt}(t)$
$\frac{ds}{dt}=(sec^2 t) -((1)t^{1-1})$
$\frac{ds}{dt}=\sec^2 t-1$

Published by
Pearson

ISBN 10:
0-32187-896-5

ISBN 13:
978-0-32187-896-0

The Derivative is:
$\frac{ds}{dt}=\sec^2 t-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.